Optimalisasi Sistem Informasi Akuntansi dalam Pengelolaan Penerimaan Kas: Upaya Pencegahan Fraud pada Usaha Kecil - Firayanti, Firayanti; Masyuri, Masyuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the optimization of accounting information systems in cash receipt management within small businesses as a strategic approach to preventing fraud risk and strengthening financial governance. The research employed a non empirical library research method using a descriptive interpretative approach through the analysis of academic literature related to accounting information systems, internal control, cash management, and fraud risk mitigation. The findings indicate that the optimization of accounting information systems contributes significantly to improving transparency, accountability, transaction monitoring, and the effectiveness of internal control mechanisms in cash receipt activities. Weak segregation of duties, inadequate documentation, limited supervision, and manual recording systems were identified as major factors increasing fraud vulnerability in small businesses. The integration of standard operating procedures and COSO based internal control frameworks strengthens sustainable fraud prevention practices and supports long term financial governance in small business environments.